Genomic Insights Into the Acid Adaptation of Novel Methanotrophs Enriched From Acidic Forest Soils - Nguyen, Ngoc-Loi; Yu, Woon-Jong; Gwak, Joo-Han; Kim, So-Jeong; Park, Soo-Je; Herbold, Craig W.; Kim, Jong-Geol; Jung, Man-Young; Rhee, Sung-Keun (Frontiers in Microbiology, 2018)
Soil acidification is accelerated by anthropogenic and agricultural activities, which could significantly affect global methane cycles. However, detailed knowledge of the genomic properties of methanotrophs adapted to acidic soils remains scarce. Using metagenomic approaches, we analyzed methane-utilizing communities enriched from acidic forest soils at pH 3 and 4 and recovered near-complete genomes of proteobacterial methanotrophs. Novel methanotroph genomes designated KS32 and KS41 belonging to two representative clades of methanotrophs (Methylocystis of Alphaproteobacteria and Methylobacter of Gammaproteobacteria) were dominant. Comparative genomic analysis revealed diverse systems of membrane transporters for pH homeostasis and defense against toxic chemicals. Various potassium transporter systems, sodium/proton antiporters, and two copies of proton-translocating F1F0-type ATP synthase genes were identified, which might participate in the key pH homeostasis mechanisms in KS32. In addition, the V-type ATP synthase and urea assimilation genes might be used for pH homeostasis in KS41. Genes involved in the modification of membranes by incorporation of cyclopropane fatty acids and hopanoid lipids might be used for reducing proton influx into cells. The two methanotroph genomes possess genes for elaborate heavy metal efflux pumping systems possibly due to increased heavy metal toxicity in acidic conditions. Phylogenies of key genes involved in acid adaptation, methane oxidation, and antiviral defense in KS41 were incongruent with that of 16S rRNA. Thus, the detailed analysis of the genome sequences provides new insights into the ecology of methanotrophs responding to soil acidification.